What drives failed policy at the World Bank? An inside account of new aid modalities to higher education: context, blame, and infallibility. Issue 2 (3rd April 2018) - Rappleye, Jeremy; Un, Leang
ABSTRACT: This article analyses recent World Bank interventions aimed at improving higher education and local research capacity in low-income countries. Our empirical entry point is a critical analysis of the Development and Innovation Grant (DIG) scheme the Bank rolled out in Cambodia (2010–2015), a virtual carbon copy export of its Academic Initiative Fund in Bangladesh. Offering a rare insider perspective, we argue that the DIG scheme ultimately failed because the Bank so glaringly misunderstood the Cambodian context. We use this case to contemplate the deeper flaws in how the Bank 'thinks', highlighting how the world's most powerful development institution manages to maintain faith in its own infallibility despite failure.